The sphere of educational services in the context of world globalization - Savyuk, L. (Економічний вісник Донбасу, 2017)
The article deals with the history of the emergence, formation and development of the knowledge economy in the context of the globalization of economic processes. The article analyzes the stages of transition and transformation of the educational services sector into the most important level of the knowledge economy. The main sectors of the economy of modern knowledge and their structural and functional features are defined. Based on the complex economic economy index, which is calculated in accordance with the methodology of the World Bank, an analysis was made of current trends in the ranking of countries in the formation of national knowledge economies. According to the analysis, it is concluded that countries with developed economic structures still occupy a leading position in the ranking of economic structures based on knowledge. However, developing countries and countries of the former USSR have the greatest rate of dynamic changes in the formation of the knowledge economy. The necessity of transition of the Ukrainian economy to the knowledge economy platform under the conditions of the third industrial revolution and its prospects in the sixth technological order is grounded. У статті розглянуто історію виникнення, становлення та розвитку економіки знань у контексті глобалізації економічних процесів. Проаналізовано етапи переходу та трансформації галузі освітніх послуг у вирішальну складову економіки знань. Визначено основні сектори сучасної економіки знань та їх структурні та функціональні особливості. На основі комплексного індексу економіки знань, що розраховується методологією Світового банку, проведений аналіз сучасних тенденцій зміни рейтингу країн світу у формуванні національних економік знань. Згідно проведеного аналізу зроблено висновок, що країни із розвиненими економічними укладами продовжують тримати лідерські позиції у рейтингу економічних укладів, заснованих на знаннях. Однак найбільший темп динамічних змін у формуванні економіки знань належить країнам, що розвиваються, та бувшим країнам СРСР. Обґрунтовано необхідність переходу економіки України на платформу економіки знань в умовах третьої промислової революції та її перспектив у шостому технологічному укладі. В статье рассмотрены история возникновения, становления и развития экономики знаний в контексте глобализации экономических процессов. Проанализированы этапы перехода и трансформации отрасли образовательных услуг в решающую составляющую экономики знаний. Определены основные сектора современной экономики знаний и их структурные и функциональные особенности. На основе комплексного индекса экономики знаний, которая рассчитывается согласно методологии Всемирного банка, проведен анализ современных тенденций изменения рейтинга стран мира в формировании национальных экономик знаний. Согласно проведенного анализа сделан вывод, что страны с развитыми экономическими укладами продолжают удерживать лидирующие позиции в рейтинге экономических укладов, основанных на знаниях. Однако наибольший темп динамических изменений в формировании экономики знаний принадлежит развивающимся странам и бывшим странам СССР. Обоснована необходимость перехода экономики Украины на платформу экономики знаний в условиях третьей промышленной революции и ее перспектив в шестом технологическом укладе.